Groups with the real chain condition on non-pronormal subgroups - Ulderico Dardano; Fausto De Mari (International Journal of Group Theory)
It is shown that a generalised radical group has no chain of non-pronormal subgroups with the same order type as the set $\mathbb{R}$ of the real numbers if and only if either the group is minimax or all subgroups are pronormal.